The four faces of nuclear terrorism - Ferguson, Charles D. (Routledge, 2005)
The growing threat -- The nuclear terrorists: who, why, and how capable? -- Seizing the bomb: theft, diversion, and instability -- Making the bomb: loose materials and know-how -- Releasing radiation: power plants and other facilities -- Dispersing radiation: the dirty bomb and other devices -- Meeting the challenge: a plan for urgent action against nuclear terrorism